(untitled) (Società e diritti, 2022)
Abstract Since ancestral times, territorial space has been a field of contention between conflicting human interests, and not only between different clans or tribes and, later, between different States of the international community, but even within the shared borders of the same State: so that we have here wondered about the essential ’juridical’ causes of this atavistic phenomenon, striving especially to grasp some ’small’ challenges won by modern constitutionalism. It is precisely in these regards that the most recent amendments to articles 9 and 41 of the constitutional text of the Italian Republic can be understood, which in relation to the territory, and its endemic history of conflict, would seem to herald potential novelties also regarding the so-called environmental ’permitting’ regime.